Tobacco Control Policy Control Policy : Strategies Successes and Setbacks - de Beyer, Joy; Waverley Brigden, Linda (Washington, DC: World Bank and Research for International Tobacco Control, 2013)
This publication was commissioned and published in the hope that descriptions of strategies, successes, and setbacks in promoting stronger tobacco control policies around the world would be of wide interest and might be useful to people grappling with similar issues. As participants in academic, advocacy, and policy meetings on tobacco control, we have been struck by the impact of real-life stories and examples. We have been educated and edified by many excellent presentations and discussions of the principles, practice, and impact of tobacco control policy - but what we remember most clearly, long after, are the stories. We have seen rooms come alive with interest and crackle with energy when people who had been at the center of efforts to develop tobacco control policy related their experiences. The case studies in this book are addressed to a wide set of readers who share an interest in health issues and policy - people in non-governmental organizations, community activists, scientists, decision-makers, health officials, and members of the public. Each story is set in the unique historical, cultural, and political environment of a particular country, but there are common threads and shared lessons that can be applied and adapted in many other countries and circumstances.